(untitled) (Advances in Civil and Architectural Engineering, 2021)
Managing personnel costs is important in all companies, especially in those whose production is labor intensive. The construction sector therefore qualifies as a suitable area for analyzing issues associated with these costs. The aim of this study is to find out whether company size affects personnel cost management under various circumstances. Four research hypotheses focus on the relationships among and the relative importance of personnel costs, use of standards, range of employee benefits offered, and economic actions taken when faced with an economic crisis. The evaluation of hypotheses is supported by using the chi-square test of independence with the aim of confirming or rejecting the statistical significance of relationships between the examined categorical variables. Results have confirmed a significant effect of company size. Several research implications and suggested future research directions are also presented in the conclusion of this paper.